1993
DOI: 10.1139/x93-264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of duration and method of herbaceous weed control on loblolly pine response through midrotation

Abstract: Herbaceous weed control studies installed by the Auburn University Silvicultural Herbicide Cooperative to examine response to methods and duration of herbaceous weed control in eight loblolly pine (Pinustaeda L.) plantations were analyzed to determine stand response through age 9. Studies were designed to compare weed control treatments with an untreated check, weed control methods (band vs. broadcast), and weed control duration (first year vs. first 2 years). Pine growth was increased by weed control on all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…The long-term positive effects on crop tree growth found for black spruce in this study are consistent with short-term results reported previously for the vegetation management studies (e.g., Lauer et al, 1993;Wood and Von Althen, 1993;Reynolds and Roden, 1995;Pitt et al, 1999;Bell et al, 2000;Sutherland and Foreman, 2000). Chemical site preparation led to significant diameter gains for both jack pine and black spruce (Fig.…”
Section: 1supporting
confidence: 92%
See 1 more Smart Citation
“…The long-term positive effects on crop tree growth found for black spruce in this study are consistent with short-term results reported previously for the vegetation management studies (e.g., Lauer et al, 1993;Wood and Von Althen, 1993;Reynolds and Roden, 1995;Pitt et al, 1999;Bell et al, 2000;Sutherland and Foreman, 2000). Chemical site preparation led to significant diameter gains for both jack pine and black spruce (Fig.…”
Section: 1supporting
confidence: 92%
“…In comparison with other methods, chemical site preparation results in better crop tree growth, particularly on competitive, nutrient-rich mixedwood sites where hardwoods and shrubs competes with planted conifers (Pitt et al, 1999;Sutherland and Foreman, 2000;Heineman et al, 2005). However, the positive effects on crop tree growth attributed to chemical site preparation in the boreal forest are based largely on short-term observations, typically 5 years after application (e.g., Lauer et al, 1993;Wood and Von Althen, 1993;Pitt et al, 1999;Sutherland and Foreman, 2000). Recent reviews (i.e., Thompson and Pitt, 2003;Wagner et al, 2004) indicate that no studies report the long-term (>10 years after application) effects of chemical site preparation on forest productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical control of woody Forest Ecology and Management 199 (2004) [231][232][233][234][235][236][237][238][239][240][241][242] competitors using herbicide has been shown to increase pine tree diameter, basal area, and volume (Bacon and Zedaker, 1987;Lauer et al, 1993;Ezell et al, 1997;Hanna, 2000). Prescribed fire, which has been commonly used in commercial pine plantations to reduce fuel loads and the risk of wildfire, can increase or decrease growth in mid-rotational loblolly pine, depending on the amount of crown scorch to the trees due to the fire (Crow and Shilling, 1980;Wade and Johansen, 1986;Lilieholm and Hu, 1987;de Ronde et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies to determine the impacts of competitive vegetation on tree growth have been carried out during the establishment phase, typically the period between planting and when canopy closure or 'site capture' occurs (Lauer et al 1993;Wagner et al 2006). In most planted forests, reduced light following canopy closure decreases the growth of the competing vegetation and the necessity for further vegetation management (Wagner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%